2013
DOI: 10.1177/0883073813493666
|View full text |Cite
|
Sign up to set email alerts
|

Large Animal Models for Batten Disease

Abstract: The neuronal ceroid lipofuscinoses, collectively referred to as Batten disease, make up a group of inherited childhood disorders that result in blindness, motor and cognitive regression, brain atrophy, and seizures, ultimately leading to premature death. So far more than 10 genes have been implicated in different forms of the neuronal ceroid lipofuscinoses. Most related research has involved mouse models, but several naturally occurring large animal models have recently been discovered. In this review, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In this respect, studies with animals that have larger brains (eg, sheep and dogs) will be required. 5,8 In addition to their larger and more complex brains for scaling up the delivery of therapies, the extent of pathology and its regionalised nature is more pronounced in the brains of sheep and dogs with NCLs than in corresponding mouse models (possibly because of the size difference), and pathology appears to more closely re semble that of human cases. 6,7 With the ability to engineer genetically modified pigs and sheep, such species might prove invaluable for further understanding the effects of the disease and to improve therapies.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, studies with animals that have larger brains (eg, sheep and dogs) will be required. 5,8 In addition to their larger and more complex brains for scaling up the delivery of therapies, the extent of pathology and its regionalised nature is more pronounced in the brains of sheep and dogs with NCLs than in corresponding mouse models (possibly because of the size difference), and pathology appears to more closely re semble that of human cases. 6,7 With the ability to engineer genetically modified pigs and sheep, such species might prove invaluable for further understanding the effects of the disease and to improve therapies.…”
Section: Pathologymentioning
confidence: 99%
“…This has necessitated a change in disease nomenclature based on the gene defect augmented with age of presentation. 4 There has been an emphasis on understanding the staging of these disorders and their molecular pathways, and advancing experimental therapies such as enzyme replacement and gene therapy in animal models, [5][6][7][8] together with the establishment of patient registries 9,10 and disease rating scales. 11,12 These efforts have culminated in the approval by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) of the first treatment for a NCL disorder: enzyme replacement therapy for neuronal ceroid lipofuscinosis type 2 (CLN2) disease.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, studies have shown AD-associated neurofibrillary accumulation (tau pathology) in normal aged sheep (Braak et al, 1994, Nelson andSaper 1995); a feature which is absent in wild type rodents and has made AD modelling challenging in rats and mice (Hardy and Selkoe 2002). While the rate of naturally occurring dementia in sheep is unknown (as most farmed sheep are culled before reaching old age), sheep with cognitive deficits are studied due to natural mutations in genes causing Battens Disease in humans (Cook et al, 2002, Jolly et al, 1980, Weber and Pearce 2013 Sheep are readily trainable for use in tests of cognitive function (Morton and Avanzo 2011) and sheep suffering from a progressive neurological disease can be quantified longitudinally using modern methods, such as EEG (Perentos et al, 2015) and MRI (Sawiak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the literature confirm that natural cases of NCL occur in a large variety of species including the bovine (19, 20). Research in prion pathology, the transmissible neurodegenerative conditions affecting human and a wide range of animal species, lead to an increased awareness of the need to use large animal models such as the bovine, in addition to conventional laboratory animals (21).…”
Section: Bovine Brain: a Translational Model For Altered Sexual Diffementioning
confidence: 79%